2005
DOI: 10.1108/01437730510617681
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture in public sector organizations

Abstract: Purpose -To provide two possible approaches for enhancing organizational culture awareness and promote cultural change in public sector organization. These approaches include training and leading by example. Design/methodology/approach -Literature outlining fundamental aspects of organizational culture is summarized, serving as a foundation for reviewing the potential value of training as a method for enhancing public managers' awareness of organizational culture. This is followed by an illustrated example of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 15 publications
1
23
0
2
Order By: Relevance
“…This paper examined the relationships between organizational culture, religious and corruption in public organization setting. Reference [12] found that training and leading by example can serve as effective methodologies for promoting culture awareness and bringing about culture change in organizations. Reference [13] stated that there is a significant influence of organizational culture toward organization performances, the effect of organization performances toward employee satisfaction, the influence of organizational culture toward customer satisfaction, and direct impact on organizational culture, based on organization performance, toward employee satisfaction.…”
Section: Organizational Culturementioning
confidence: 99%
“…This paper examined the relationships between organizational culture, religious and corruption in public organization setting. Reference [12] found that training and leading by example can serve as effective methodologies for promoting culture awareness and bringing about culture change in organizations. Reference [13] stated that there is a significant influence of organizational culture toward organization performances, the effect of organization performances toward employee satisfaction, the influence of organizational culture toward customer satisfaction, and direct impact on organizational culture, based on organization performance, toward employee satisfaction.…”
Section: Organizational Culturementioning
confidence: 99%
“…Concerning the level of analysis, the experts judged that most of the factors apply to departments and some are specific to types of learners. While analyzing culture on a micro-level (individual preferences) should be avoided, the importance of subcultures such as learnertypes is seen as valid and insightful (Arellano-Gault, 2013;Rahman et al, 2013;Schraeder et al, 2005). Concerning the role of political values like bureaucracy , evaluated factors show sensibility.…”
Section: Discussionmentioning
confidence: 99%
“…Superiors play a major role to sustain learning activities, invoke change, training programs and knowledge management initiatives (Schraeder, tears, & Jordan, 2005;Rahman et al, 2013;Greiling & Halachmi, 2013;Yao et al, 2007;. Hence, the question is not whether or not support needs to be provided, but what kind of support is required.…”
Section: Culture In Open E-learning Systemsmentioning
confidence: 99%
See 2 more Smart Citations